Avaliação da qualidade da água de cinco córregos urbanos como subsídio à gestão dos recursos hídricos - Andrade, Caroline Simonato Silva (2015)
The sub-basins of the Barbado, Gambá, Ribeirão do Lipa and São Gonçalo streams, and the micro-basin of Mãe Bonifácia stream are part of the urban area of Cuiabá-MT and are the most relevant sub-basins of greatest importance by human influence, beyond we are tributaries of the river basin Cuiabá, a major river in the Pantanal wetland and environmental importance to Brazil and the world. Given the importance that water resources can have for regional development, this study aims to assess the water quality in order to support the management of the sub-basins of the Barbado, Ribeirão do Lipa, Gambá and São Gonçalo streams, and watershed stream Mãe Bonifácia, located in the urban area of the city of Cuiabá in Mato Grosso. To this aim, surface water samples were collected near the spring and rivermouth, in March, June, October and December 2014. The variables studied were: electrical conductivity, turbidity, color, water temperature, pH, dissolved oxygen, nitrate, nitrite, phosphate, sulfate, chloride, ammonia, total nitrogen Kjeldahl, biochemical oxygen demand, chemical oxygen demand, total phosphorus, aluminum, iron, manganese, cadmium, chromium, copper, nickel and lead. The results of the variables showed temporal and spatial relations, with the worsening of most variables in the rainy season and rivermouth. The Pearson correlation showed the relationship between the variables and the hierarchical cluster analysis (AHA) identified the existence of three groups of the studied streams, being the Group A formed by the Barbado and Gambá streams, Group B formed by Ribeirão do Lipa and São Gonçalo streams and Group C only by the Mãe Bonifácia stream. To assess the quality of the groups, a discriminant analysis (DA) showed correct classification in 69% of samples from streams, being possible, in the "stepwise forward", reduce the number of variables collected maintaining the effectiveness of the classification of space groups. The principal component analysis (PCA/AF) which identified the representative variables in each group allowed also distinguish those responsible for spatial variations and sources of origin. Of these groups, the Group C was the one with the worst water quality, reflecting the diverse urban and as the use and occupation of the drainage area contributions interfere with the water resource. Thus, the review of the goals and framework becomes necessary for the proper management of each urban stream.